2020
DOI: 10.1002/mgg3.1217
|View full text |Cite
|
Sign up to set email alerts
|

Two novel mutations of PAX3 and SOX10 were characterized as genetic causes of Waardenburg Syndrome

Abstract: BackgroundThe objective of this study was to investigate the genetic causes of two probands diagnosed as Waardenburg syndrome (WS type I and IV) from two unrelated Chinese families.MethodsPAX3 and SOX10 were the main pathogenic genes for WS type I (WS I) and IV (WS IV), respectively; all coding exons of these genes were sequenced on the two probands and their family members. Luciferase reporter assay and co‐immunoprecipitation (CO‐IP) were conducted to verify potential functional outcomes of the novel mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…SOX10 encodes a TF critical to the early development of neural crest stem cells by promoting cell survival and maintaining multipotency [46, 47]. Moreover, SOX10 controls the development of melanocytes by regulating MITF expression in synergy with PAX3 [11]. Through modulation of RET expression, SOX10 determines the morphogenesis of the enteric nervous system (ENS) [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SOX10 encodes a TF critical to the early development of neural crest stem cells by promoting cell survival and maintaining multipotency [46, 47]. Moreover, SOX10 controls the development of melanocytes by regulating MITF expression in synergy with PAX3 [11]. Through modulation of RET expression, SOX10 determines the morphogenesis of the enteric nervous system (ENS) [48].…”
Section: Discussionmentioning
confidence: 99%
“…WS presents with a high degree of genetic heterogeneity. Six genes have been confirmed to cause WS: paired box 3 ( PAX3 ) [8], melanocyte inducing transcription factor ( MITF ) [9, 10], SRY-box transcription factor 10 ( SOX10 ) [5, 11], endothelin 3 ( EDN3 ) [12], endothelin receptor type B ( EDNRB ) [13], and snail family transcriptional repressor 2 ( SNAI2 ) [14]. Variants in PAX3 are primarily responsible for WS1 and WS3, while SOX10, EDN3 , and EDNRB variants are involved in WS4.…”
Section: Introductionmentioning
confidence: 99%
“…SOX10 possesses a dimerization domain (AA61-101), a DNA-binding high-mobility group (HMG) domain (101–180), a conserved domain in the center of the protein (233–306), and a transactivation domain (400–466) at the C-terminus. Mutations in SOX10 are associated with WS2E and WS4C (OMIM: 613,266), while mutations in SOX10 that are responsible for WS4 with neurological features referred to as PCWH (OMIM: 609,136) which patients may suffer from peripheral neuropathy, mental retardation, cerebellar ataxia, neonatal hypotonia and spasticity [ 5 , 14 , 46 48 ]. PCWH is mostly caused by truncating mutations in the last coding exon of SOX10 or less than 50–55 nucleotides upstream of the last coding exon, induce escaping the mutant mRNAs from the NMD pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The PD and HD are DNA binding domains, while the TA domain mediates transcriptional regulation. The translated regions encode a 505-amino acid protein [ 5 , 19 , 48 , 50 , 51 ]. A previous functional study has demonstrated that the truncating mutation 1185 insTGA which removes a part of the transactivation domain of PAX3 reduced its effect on MITF promoter activation, and also its synergistic effect with SOX10 was completely lost.…”
Section: Discussionmentioning
confidence: 99%
“…WS is caused by the lack of melanophores in the eyes, skin, cochlea, and hair, which in itself originates from mutations in different genes affecting neural crest function (Alehabib et al, 2020 ). The known causative genes of WS include PAX3, MITF, WS2B, WS2C, SNAI2, EDNRB, EDN3, SOX10 , and TYR ; among them, PAX3 is the most classic, and its mutations or gross deletions produce WS1 or WS3 (Yu et al, 2020 ). To date, heterozygous mutations of PAX3 are commonly associated with WS1, whereas partial or total deletions of PAX3 are often observed in WS3 cases (Ahmed Jan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%